Role Of Literary Societies to The Development of Mahjar Literature: A Study - Mofidul Alom Talukdar (AG Volumes, 2022)
During the late of the 19th and early 20th century, a new genre of Arabic literary movement was produced entitled as ‘Mahjar Literature’ both in the North and the South Americas by some Arab immigrants; especially from Syria and Lebanon. Most of them were writers, poets, philosophers, thinkers and literary scholars. The Mahjar writers, influenced by the western literary thoughts, united around the multiplex literary societies which they established in sequence to promote and develop their literatures. As a prominent objective, these literary societies were created both in the North and the South Americas to preserve Arabic language, to develop their literature, to produce new ideas and to bring the innovations of the ‘New World’. Among these literary societies, the two prominent literary societies viz. Al- Rabitah Al- Qalamiyyah (The Pen League Association) and Al-Usbah al-Andalusiyyah (The Andalusian League) which played a significant role to the development of Mahjar literature. In this article, an attempt has been made to analyze these literary societies which emerged to introduce a great role to the development of the Mahjar literature in this ‘New World’.